Given: A circle, \[2{{x}^{2}}+2{{y}^{2}}=5\] and a parabola, \[{{y}^{2}}=4\sqrt{5}x\].
Statement-I: An equation of a common tangent to these curves is \[y=x+\sqrt{5}x\].
Statement-II: if the line, \[y=mx+\dfrac{\sqrt{5}}{m},\left( m\ne 0 \right)\] is their common
tangent, then m satisfies \[{{m}^{4}}-3{{m}^{2}}+2=0\].
(1) Statement-I is true, Statement-II is true; Statement-II is a correct explanation for Statement-I.
(2) Statement-I is true, Statement-II is true; Statement-II is not a correct explanation for Statement-I.
(3) Statement-I is true, Statement-II is false.
(4) Statement-I is False, Statement-II is true.
Answer
Verified
512.7k+ views
Hint: Consider a tangent expression \[y=mx+\dfrac{a}{m}\] for the given parabola. For being
a common tangent, the tangent expression we created for parabola should also act as
tangent to the circle. Thus, equating the distance between the center of the circle and the
tangent expression will lead us to find the common tangent.
The given circle \[2{{x}^{2}}+2{{y}^{2}}=5\]can be rewritten as:
\[{{x}^{2}}+{{y}^{2}}=\dfrac{5}{2};\]
Therefore, the center of this circle is \[\left( 0,0 \right)\] and the radius is
\[\sqrt{\dfrac{5}{2}}\]units.
For any parabola \[{{y}^{2}}=4ax;\] the tangent of the parabola with slope ‘m’ is considered
as \[y=mx+\dfrac{a}{m}\].
Subsequently, the tangent to the parabola \[{{y}^{2}}=4\sqrt{5}x\] can be taken as:
\[y=mx+\dfrac{\sqrt{5}}{m};\]
Which can be rewritten as:
\[my={{m}^{2}}x+\sqrt{5}\];
As it was mentioned that the parabola and circle have a common tangent:
Then, the distance between \[\left( 0,0 \right)\] and \[my={{m}^{2}}x+\sqrt{5}\] is equal to
the radius of the circle.
Therefore, applying the distance formula,
\[\dfrac{\left| {{m}^{2}}\left( 0 \right)-m\left( 0 \right)+\sqrt{5} \right|}{\sqrt{{{\left(
{{m}^{2}} \right)}^{2}}+{{\left( -m \right)}^{2}}}}=\dfrac{\sqrt{5}}{2}\]
\[\dfrac{\sqrt{5}}{\sqrt{{{m}^{4}}+{{m}^{2}}}}=\dfrac{\sqrt{5}}{2}\]
Now, let us do squaring on both sides to simplify further;
\[2=\left( {{m}^{4}}+{{m}^{2}} \right)\]
\[\Rightarrow {{m}^{4}}+{{m}^{2}}+2=0\]
\[({{m}^{2}}+2)({{m}^{2}}-1)=0\]
\[\therefore {{m}^{2}}=1,{{m}^{2}}=-2\]
As \[{{m}^{2}}=-2\] is not valid, we shall consider \[m=\pm 1\].
So, the common tangents can be:
\[y=x+\sqrt{5}\], by substituting \[m=1\].
\[y=-x-\sqrt{5}\], by substituting \[m=-1\].
Now, for statement II:
On Solving;
\[\begin{align}
& {{m}^{4}}-3{{m}^{2}}+2=0 \\
& {{m}^{4}}-2{{m}^{2}}-{{m}^{2}}+2=0 \\
& \left( {{m}^{2}}-2 \right)\left( {{m}^{2}}-1 \right)=0 \\
\end{align}\]
We do have \[{{m}^{2}}=1\] from this expression, but it is not the same expression as
statement I.
So, both the statements are correct, but statement II is not the correct explanation of
statement I.
Hence, option b is the correct answer.
Note: You may also start the procedure by considering a common tangent expression with
respect to the given circle.
Also, as a square of a number can never be negative, we ignored \[{{m}^{2}}=-2\] as a
solution.
a common tangent, the tangent expression we created for parabola should also act as
tangent to the circle. Thus, equating the distance between the center of the circle and the
tangent expression will lead us to find the common tangent.
The given circle \[2{{x}^{2}}+2{{y}^{2}}=5\]can be rewritten as:
\[{{x}^{2}}+{{y}^{2}}=\dfrac{5}{2};\]
Therefore, the center of this circle is \[\left( 0,0 \right)\] and the radius is
\[\sqrt{\dfrac{5}{2}}\]units.
For any parabola \[{{y}^{2}}=4ax;\] the tangent of the parabola with slope ‘m’ is considered
as \[y=mx+\dfrac{a}{m}\].
Subsequently, the tangent to the parabola \[{{y}^{2}}=4\sqrt{5}x\] can be taken as:
\[y=mx+\dfrac{\sqrt{5}}{m};\]
Which can be rewritten as:
\[my={{m}^{2}}x+\sqrt{5}\];
As it was mentioned that the parabola and circle have a common tangent:
Then, the distance between \[\left( 0,0 \right)\] and \[my={{m}^{2}}x+\sqrt{5}\] is equal to
the radius of the circle.
Therefore, applying the distance formula,
\[\dfrac{\left| {{m}^{2}}\left( 0 \right)-m\left( 0 \right)+\sqrt{5} \right|}{\sqrt{{{\left(
{{m}^{2}} \right)}^{2}}+{{\left( -m \right)}^{2}}}}=\dfrac{\sqrt{5}}{2}\]
\[\dfrac{\sqrt{5}}{\sqrt{{{m}^{4}}+{{m}^{2}}}}=\dfrac{\sqrt{5}}{2}\]
Now, let us do squaring on both sides to simplify further;
\[2=\left( {{m}^{4}}+{{m}^{2}} \right)\]
\[\Rightarrow {{m}^{4}}+{{m}^{2}}+2=0\]
\[({{m}^{2}}+2)({{m}^{2}}-1)=0\]
\[\therefore {{m}^{2}}=1,{{m}^{2}}=-2\]
As \[{{m}^{2}}=-2\] is not valid, we shall consider \[m=\pm 1\].
So, the common tangents can be:
\[y=x+\sqrt{5}\], by substituting \[m=1\].
\[y=-x-\sqrt{5}\], by substituting \[m=-1\].
Now, for statement II:
On Solving;
\[\begin{align}
& {{m}^{4}}-3{{m}^{2}}+2=0 \\
& {{m}^{4}}-2{{m}^{2}}-{{m}^{2}}+2=0 \\
& \left( {{m}^{2}}-2 \right)\left( {{m}^{2}}-1 \right)=0 \\
\end{align}\]
We do have \[{{m}^{2}}=1\] from this expression, but it is not the same expression as
statement I.
So, both the statements are correct, but statement II is not the correct explanation of
statement I.
Hence, option b is the correct answer.
Note: You may also start the procedure by considering a common tangent expression with
respect to the given circle.
Also, as a square of a number can never be negative, we ignored \[{{m}^{2}}=-2\] as a
solution.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Draw a labelled sketch of the human eye class 12 physics CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
What are the major means of transport Explain each class 12 social science CBSE